"Tu, czyli tam". O czasie i szacunku (wybrane aspekty prozy Krzysztofa Fedorowicza) = "Here that is there". On time and reverence (chosen aspects of Krzysztof Fedorowicz prose) - Sztyber, Radosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The sketch is an attempt to present two books by Krzysztof Fedorowicz released in 2012 ("Grünberg") and 2020 ("Zaświaty. Opowieści o nieprzemijaniu" ["Afterworlds. Stories on everlasting"]) in the perspective of their time complexity. The matter draws attention in the novels particularly. Apparent or even real past stories are narrated in the present tense(s) intentionally that results in leader`s seeing the facts "in statu nascendi".
Keywords: Fedorowicz, Krzysztof (1970- ); narracja; czas; historia; szacunek; narration; time; history; reverence